Kekerasan Seksual dan Viktimisasi Korban Perempuan : Analisis Melalui Lensa Teori Kriminologi Feminisme - Keisha Keisha (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Sexual violence is not only a criminal matter, but also an attack on human rights. It is important to view sexual violence as a crime that undermines the dignity and integrity of individuals, both men and women. Despite recent advances in gender equality, traditional views of women as weak and subordinate still influence societal attitudes. This can exacerbate the victimization of women and make law enforcement more difficult. Therefore, there is a need for an inclusive approach to involve men in the prevention of sexual violence. Feminist criminology theory helps both researchers and readers broaden their understanding of sexual violence by highlighting its underlying structural and cultural aspects. This approach addresses gender inequality in law enforcement policies and gives voice to victims who are often ignored. Measures to prevent victimization include public education, better access to support services, increased awareness of victims' rights, and improved law enforcement systems that are responsive and fair.